Students Self-Regulated Learning and English Achievement - Pungus, Rini Novrita; Frans, Nofry (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The purpose of this study was to investigate the level of student self-regulated learning and the level of student English achievement. In addition to that, this study also wanted to find out whether there was the effect of student self-regulated learning on English achievement and which of those self-regulated learning strategies predicted English achievement. This research utilized a quantitative research design, and a questionnaire from Magno was adapted for this study. This study involved four hundred students of Science and Social classes at Sekolah Menengah Atas Negeri Satu Langowan as population, and there were one hundred sixty-nine students as the sample. The results showed that the students' level of self-regulated learning was categorized as highly self-regulated. Second, their level of English achievement was classified as high. Third, the results showed that self-regulated learning significantly affected English achievement. Finally, the best predictor of English achievement could be computed because heteroscedasticity was present. Consequently, multiple regression cannot be performed. Self-regulated learning is an essential part of the learning process. It is related to motivation, learning, and achievement that students have to apply in their learning environment daily to reach the effectiveness and efficiency of learning output. Keywords : English Achievement, Student Self-Regulated Learning